A Household-Level Investigation of Women Empowerment and Migration Intention: The Case of Afghanistan - Esra Karapınar Kocağ (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
This study investigates the relationship between two important concerns, which are migration intentions of households and women empowerment in the case of Afghanistan where migration is a process that continues from its history to the present, and international indicators shows a quite bad picture on women empowerment or gender equality. It is obvious that women in this country presents a great vulnerability and they need to be empowered. However, it is not that obvious whether their empowerment is associated with migration intention of households. Therefore, this paper questions how and in which way the empowerment of women as a vulnerable group within different segments of Afghan society influence migration intention of households. Findings show that women empowerment measures, that are Women_leader, Women_support, Women_job, and Girls_edu, do not significantly influence migration intentions of households when they exist separately. However, it significantly influence migration intentions when they are allowed to interact together. It might be said that empowerment of women from political, social, and economic aspects that are presented by four of abovementioned measures is important to explain potential movements of population. Besides, there is significant regional differences to explain migration intentions. These findings are expected to be useful for policy makers on migration policies.